Longshore Spatial and Temporal Variation in Cape Cod National Seashore - Jones, Sarah (East Carolina University, 2017)
Beach and dune systems are dynamic environments where changes occur from season to season due to a continual influx of energy from waves, currents, and winds. For coasts to best be managed, and to protect or preserve valuable natural and economic resources, the process-form relationship between beach and dune systems needs to be better understood. It is, therefore, necessary to look at these features at a variety of spatial and scalar resolutions. Throughout history, the relationship between both systems have been found to act coincidentally with one another, but somehow the interaction has rarely been looked at. This exploratory research investigates the different methodologies that are used to obtain and monitor coastal changes in the alongshore variation of the shoreline and duneline to try and find the most accurate approaches in terms of sample length/location and optimal transect spacing interval. This study focuses on two different sized zones (3.89km and 6.4km long) in the Province Lands Dunes area of Cape Cod National Seashore. Both areas are characterized by beach segments backed by a line of foredunes. GIS, DSAS and remotely sensed data sources are used to quantify and describe both shoreline and duneline changes based off of orthoimagery from 2001-2012 time periods. To analyze the data from DSAS, visual and statistical analyses are completed and compared to one another to answer the proposed research questions.
Keywords: duneline; DSAS; Cape Cod National Seashore (Mass.); Shorelines--Monitoring--Massachusetts; Sand dunes--Massachusetts